Comprehensive Wealth and Future Consumption: - Ferreira, Susana; Hamilton, Kirk; Vincent, Jeffrey R. (World Bank, 2012)
Economic theory predicts that the current change in national wealth, broadly defined to include natural and human capital as well as produced capital ("genuine savings"), determines whether the present value of future changes in consumption is positive or negative. Theoretical research has focused on the effects of population growth on this relation, but no rigorous empirical investigation has been conducted. Panel data for 64 developing countries during 1970–82 are used to test the effects of three adjustments for population growth, including one that controls for omitted wealth. Although the adjustments have substantial impacts on estimates of genuine savings, they lead to only limited improvements in the relation between those estimates and subsequent consumption changes. Even without adjustments for population growth, adjustments for natural resource depletion improve the relation significantly. Policymakers and economists can interpret published estimates of genuine savings as signals of future consumption paths if and only if the estimates include adjustments for natural resource depletion. But better estimates of capital stocks are needed before it can be confidently said that adjustments for population growth significantly improve the accuracy of those signals.